Public pollution abatement and wage inequality. Issue 2 (17th February 2019) - Pi, Jiancai; Shi, Shenyu
ABSTRACT: This paper constructs three-sector general equilibrium models to investigate how public pollution abatement affects the skilled–unskilled wage inequality. In the basic model with full employment, we find that a higher degree of public pollution abatement will decrease the wage inequality if the intensity of skilled labor in the urban skilled sector is sufficiently large and expand or narrow down the wage gap if this intensity is sufficiently small. In the extended models, we consider other four cases, and obtain the results similar or dissimilar to that of the basic model.